#### Answer

$= \frac{m+3}{2m+1}$

#### Work Step by Step

$\frac{m+3}{2(m+3)-5}$
$= \frac{m+3}{2(m+3)-5}$
$= \frac{m+3}{2m+6-5}$
$= \frac{m+3}{2m+1}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$= \frac{m+3}{2m+1}$

$\frac{m+3}{2(m+3)-5}$
$= \frac{m+3}{2(m+3)-5}$
$= \frac{m+3}{2m+6-5}$
$= \frac{m+3}{2m+1}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.